INSTITUTIONAL ENSURING PERSONNEL SECURITY OF BUSINESS STRUCTURES (Development Service Industry Management, 2024)
The management of personnel security in a modern enterprise is an extremely urgent issue, especially in the conditions of constant changes in legislation and challenges related to the state of war in Ukraine. The article examines the main legislative acts regulating personnel security in Ukraine, which include: the Constitution of Ukraine, the Labor Code, the Law "On Labor Protection", the Law "On Mandatory State Social Insurance", the Law "On Labor Compensation" , ZU "On employment of the population", ZU "On personal data protection", ZU "On the basic principles of ensuring cyber security of Ukraine", ZU "On collective contracts and agreements", ZU "On vacations", ZU "On professional development of employees", ZU "On health care", ZU "On social dialogue in Ukraine", ZU "On insurance". These legislative acts provide a comprehensive approach to the regulation of personnel security at the enterprise. In addition, the article presents in graphic form the concept of personnel security management of the enterprise, which is based on a systematic approach to ensuring stability, protection and development of personnel potential. The specified concept includes general provisions (in particular, security, enterprise personnel, personnel risks and information confidentiality), principles of personnel security management (in particular, systematicity, adaptability, continuity, transparency, compliance with legislation), goals (protection against personnel risks, ensuring the stability of personnel, increasing qualifications and development of employees, provision of effective communication and interaction, development of employee loyalty and corporate culture, provision of social and legal protection of employees), components of personnel security (anti-conflict, vital activity, health, intellectual, informational, career, pension and insurance, professional, psychological, social-motivational, technological, physical, financial), objects of protection (enterprise personnel and its actions, information resources, social-psychological climate, reputation, objects of intellectual property), legal protection.
Keywords: security; personnel security; personnel security management; legislative acts; concept; principles; objects of protection